Introduction: The Cultural Study of Commercial Sex: Taking a policy perspective. Issue 1 (8th December 2014) - Hammond, Natalie; Attwood, Feona
Abstract : The transformation of the sex industry since 2000 has meant that the image of the 'street prostitute' touting for business on dark street corners is less representative of sex work or sex workers than it has ever been. Much of our knowledge about the sex industry, and about wider transformations of economic, intimate and cultural life, is out of date (Bernstein, 2007a ), and policy processes are taking place within the context of limited or outdated knowledge. The growth in visibility, consumption and diversity of sexual commerce is now well recognised (Weitzer, 2000 ; Agustín, 2005 ; Scoular and Sanders, 2010 ) and commercial sex industries are known to operate across a variety of locations, and within specific modes of production and consumption, which are historically, contextually and culturally contingent and where 'the meaning of buying and selling sex is not always the same' (Agustín, 2005 : 619).